Relief learning requires a coincident activation of dopamine D1 and NMDA receptors within the nucleus accumbens. (1st March 2017) - Bergado Acosta, Jorge R.; Kahl, Evelyn; Kogias, Georgios; Uzuneser, Taygun C.; Fendt, Markus
Abstract: Relief learning is the association of a stimulus with the offset of an aversive event. Later, the now conditioned relief stimulus induces appetitive-like behavioral changes. We previously demonstrated that the NMDA receptors within the nucleus accumbens (NAC) are involved in relief learning. The NAC is also important for reward learning and it has been shown that reward learning is mediated by an interaction of accumbal dopamine and NMDA glutamate receptors. Since conditioned relief has reward-like properties, we hypothesized that (a) acquisition of relief learning requires the activation of dopamine D1 receptors in the NAC, and (b) if D1 receptors are involved in this process as expected, a concurrent dopamine D1 and NMDA receptor activation may mediate this learning. The present study tested these hypotheses. Therefore, rats received intra-NAC injections of the dopamine D1 receptor antagonist SCH23390 and the NMDA antagonist AP5, either separately or together, at different time points of a relief conditioning procedure. First, we showed that SCH23390 dose-dependently blocked acquisition and the expression of conditioned relief. Next, we demonstrated that co-injections of SCH23390 and AP5 into the NAC, at doses that were ineffective when applied separately, blocked acquisition but not consolidation or expression of relief learning. Notably, neither of the injections affected the locomotor response of the animals to the aversive stimuli suggesting that their perception is not changed. This data indicates that a co-activation of dopamine D1 and NMDA receptors in the NAC is required for acquisition of relief learning. Graphical abstract: Highlights: Backward pairing of CS and US leads to relief learning. Nucleus accumbens dopamine D1 receptors are involved in relief learning. Low doses of a D1 or NMDA antagonist, injected alone, do not affect relief learning. Combined injections of low doses of a D1 or NMDA antagonist block relief learning. This indicates that a coincident D1/NMDA activation is crucial for relief learning.